Maternal substance use disorder predicting children's emotion regulation in middle childhood: the role of early mother-infant interaction - Punamäki RL; Flykt M; Belt R; Lindblom J (ELSEVIER SCI LTD, 2022)
Background: Maternal prenatal substance use disorder (SUD) represents a dual risk for child wellbeing due to teratogenic impacts and parenting problems often inherent in SUD. One potential mechanism transferring this risk is altered development of children's emotion regulation (ER). The present study examines how mother's prenatal SUD and early mother-infant interaction quality predict children's ER in middle childhood.
Method: The participants were 52 polysubstance using mothers and 50 non-users and their children. First-year mother-infant interaction quality was assessed with the Emotional Availability (EA) Scales and children's ER with the Children's Emotion Management Scales (CEMS), and its parent version (P-CEMS) at 8-12 years.
Results: Mother's prenatal SUD predicted a low level of children's adaptive ER strategies, whereas early mother-infant interaction problems predicted a high level of emotion dysregulation. The dyadic interaction also mediated the effect of SUD on emotion dysregulation. In the SUD group, more severe substance use predicted high emotion inhibition.
Conclusion: Early mother-infant interaction quality is critical in shaping children's ER, also in middle-childhood. Interventions aimed for mothers with prenatal SUD should integrate parenting components to support the optimal development of multiply vulnerable children.